(untitled) (The Review of Diabetic Studies, 2025)
Background: Diabetes mellitus represents a major public health challenge worldwide, with an increasing prevalence in Saudi Arabia. The complexity of diabetes management requires integrated, multidisciplinary approaches involving professionals from health administration, radiology, laboratory medicine, and nursing to ensure optimal outcomes and coordinated patient care. Objective: This systematic review aimed to explore and synthesize available evidence on integrated care models for diabetes management in Saudi Arabia, emphasizing the multidisciplinary roles of health administrators, radiologists, laboratory specialists, and nurses. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a comprehensive literature search was conducted across major databases including PubMed, Scopus, Web of Science, and Google Scholar. A total of 1,042 articles were initially identified. After screening titles, abstracts, and full texts according to predefined inclusion and exclusion criteria, 19 studies were included in the final review. Data were extracted and analyzed thematically to identify key patterns and multidisciplinary contributions within integrated care models. Results: The findings highlighted that integrated care models significantly improve patient outcomes, continuity of care, and resource utilization in diabetes management. Health administration played a crucial role in policy development and system coordination, while radiology and laboratory services provided essential diagnostic and monitoring support. Nursing contributed through patient education, follow-up, and adherence support. However, challenges such as fragmented communication and limited interprofessional collaboration were noted in several studies. Conclusion: This systematic review underscores the importance of a structured, multidisciplinary approach in diabetes management within the Saudi healthcare system. Strengthening coordination between administrative, clinical, and diagnostic teams is vital for enhancing care quality and achieving better patient outcomes. Future studies should focus on developing localized frameworks that foster effective integration across all healthcare disciplines involved in diabetes care.